Catalytic, Cascade Ring‐Opening Benzannulations of 2, 3‐Dihydrofuran O, O‐ and N, O‐Acetals. Issue 30 (15th June 2016) - Aponte‐Guzmán, Joel; Phun, Lien H.; Cavitt, Marchello A.; Taylor, J. Evans; Davy, Jack C.; France, Stefan
Abstract: An Al(OTf)3 ‐catalyzed intramolecular cascade ring‐opening benzannulation of 2, 3‐dihydrofuran O, O ‐ and N, O ‐acetals is described. The cascade sequence involves the dihydrofuran ring‐opening by acetal hydrolysis, an intramolecular Prins‐type cyclization, and aromatization to generate an array of benzo‐fused (hetero)aromatic systems in up to 95 % yield. This method represents the first example of dihydrofuran acetal usage in benzannulation reactions. The approach provides excellent regiocontrol based on the choice of alkenes used to form the requisite dihydrofuran acetals. Abstract : An intramolecular cascade ring‐opening benzannulation of 2, 3‐dihydrofuran (DHF) acetals is disclosed, which generates highly functionalized benzannulation products, including naphthalenes, benzofurans, benzothiophenes, and dibenzofurans. When the DHF acetal is substituted at the 5‐position with 1‐pyrroles or 1‐indoles, the ring‐opening cyclization occurs without aromatization to afford tetrahydroindolizines or hydropyrido[1, 2‐a]indoles, respectively.